A Powerful CD8+ T‐Cell Stimulating D‐Tetra‐Peptide Hydrogel as a Very Promising Vaccine Adjuvant. Issue 5 (14th November 2016) - Luo, Zichao; Wu, Qinjie; Yang, Chengbiao; Wang, Huaimin; He, Tao; Wang, Youzhi; Wang, Zhongyan; Chen, Hao; Li, Xingyi; Gong, Changyang; Yang, Zhimou
Abstract : A novel vaccine adjuvant based on a supramolecular hydrogel of a D‐tetra‐peptide is reported. Antigens can be easily incorporated into the hydrogel by a vortex or by gently shaking before injection. The vaccines can stimulate strong CD8+ T‐cell responses, which significantly inhibits tumor growth. This novel adjuvant is expected to enable a wide range of sub‐unit vaccines and help the production of antibodies.